(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the epidemiological and clinical features of congenital esophageal atresia (EA) and evaluate treatment outcomes, as well as early postoperative complications after EA repair at Nghe An Obstetrics and Pediatrics Hospital. Materials and methods: A descriptive cross-sectional study of 32 patients diagnosed and surgically treated for congenital esophageal atresia at Nghe An Obstetrics and Pediatrics Hospital from January 2021 to June 2024. Results: The male-to-female ratio was 1.5/1. The most common symptom leading to hospitalization was respiratory failure, which accounted for 84.38%. According to Waterson classification, EA type C was predominant with 29 cases accounted for 90.62%, and the percentage of EA type A was 46.88%. Based on the Spitz classification, most patients were classified in group I, accounting for 56.25%. Early post-operative complications included esophageal fistula in 28.12%, postoperative pneumonia in 59.37%, sepsis in 34.37%, anastomotic stricture in 9.37%, and surgical wound bleeding in 6.25%. The survival rate after EA surgery was 71.88%. Conclusions: Accurately identifications of the gap between the two ends of the esophagus is crucial for deciding the surgical method, timing of surgery, and postoperative care in order to reduce the incidence of anastomotic fistula. Sufficient critical care is essential in minimizing the rates of pneumonia and sepsis during post-operative period, which ultimately reduce mortality.